A prospective comparative study of metabolic and haematological profile of infants born to mothers with pregestational and gestational diabetes mellitus - Vemuri, Sravani; Vannala, Raju (International Journal of Contemporary Pediatrics, 2022)
Background: Diabetes mellitus during pregnancy has long been associated with maternal and neonatal morbidity and mortality. Gestational and pregestational diabetes make up the most common maternal metabolic disorder of pregnancy. Suboptimal control of blood glucose has the potential for serious neonatal adverse effects. Neonates of pregestational diabetic mothers are at risk for congenital malformations, perinatal mortality, preeclampsia, preterm birth, increased birthweight, neonatal hypoglycaemia. Methods: 100 neonates born to diabetic mothers were enrolled in the study during 1January 2019 to 30June 2020 at Mediciti institute of medical sciences, Telangana. Gestational age, birth weight, relevant antenatal history of mothers with diabetes mellitus and examination findings were collected and recorded. Blood samples were collected to perform relevant biochemical tests and managed as per unit protocol. Results: Of the 100 neonates, 93% were born to mothers with GDM, while the remaining 7% were born to mothers with PGDM. 39% (39/100) of mothers had poor glycemic control. Mean birth of neonates born to PGDM mothers was lower when compared to GDM and was statistically significant (p=0.02). Hyperbilirubinemia was the most common abnormality seen in 53% of neonates. Incidence of hypoglycemia, hypocalcemia, hypomagnesemia, polycythemia, hyperbilirubinemia, were higher in infants born to mothers with PGDM and was statistically significant. Conclusions: Among the pregnancies complicated by diabetes, PGDM continues to have a major contribution. Metabolic and haematological complications are more in neonates born to mothers with PGDM. Hypocalcemia and hyperbilirubinemia was the most common complications in IDM.